Cost-Effectiveness Analysis of a Military Hearing Conservation Program. Issue 9 (7th February 2018) - Garcia, Seth L; Smith, Kenneth J; Palmer, Catherine
Abstract: Introduction: Occupational noise threatens U.S. worker health and safety and commands a significant financial burden on state and federal government worker compensation programs. Previous studies suggest that hearing conservation programs have contributed to reduced occupational hearing loss for noise-exposed workers. Many military personnel are overexposed to noise and are provided hearing conservation services. Select military branches require all active duty personnel to follow hearing conservation program guidelines, regardless of individual noise exposure. We evaluated the cost-effectiveness of a military hearing conservation program, relative to no intervention, in relation to cases of hearing loss prevented. Methods: We employed cost-effectiveness analytic methods to compare the costs and effectiveness, in terms of hearing loss cases prevented, of a military hearing conservation program relative to no program. We used costs and probability estimates available in the literature and publicly available sources. The effectiveness of the interventions was analyzed based on whether hearing loss occurred over a 20-yr time frame. Results: The incremental cost-effectiveness ratio of the hearing conservation program compared with no intervention was 10, 657 per case of hearing loss prevented. Workers were 28% less likely to sustain hearing loss in our model when they received the hearing conservation program compared with no intervention, which reflected the greater effectiveness of the hearing conservation program. Cost-effectiveness results were sensitive to estimated values for the probability of acquiring hearing loss from both interventions and the cost of hearing protection. We performed a Monte Carlo probabilistic sensitivity analysis where we simultaneously varied all the model parameters to their extreme plausible bounds. When we ran 10, 000 Monte Carlo iterations, we observed that the hearing conservation program was more cost-effective in 99% of cases when decision makers were willing to pay 64, 172 per case of hearing loss prevented. Conclusions: Conceding a lifetime cost for service-related compensation for hearing loss per individual of 64, 172, the Department of Defense Hearing Conservation Program is an economically reasonable program relative to no intervention, if a case of hearing loss avoided costs 10, 657. Considering the net difference of the costs and comparative benefits of both treatment strategies, providing a hearing conservation program for all active duty military workers may be a cost-effective intervention for the Department of Defense.